ToF‐SIMS study of phosphorus diffusion in low‐dimensional silicon structures. (18th May 2012) - Perego, Michele; Seguini, Gabriele; Fanciulli, Marco
<x xml:space="preserve">Abstract</x> Doping of Si nanocrystals is expected to be crucial in order to tailor the properties of these nanostructures and to implement their technological applications. In this work, phosphosilicate ultra‐thin films (P δ‐layers) were buried in an SiO/SiO2 multilayer structure, and the redistribution of P atoms during high‐temperature (800–1100 °C) thermal treatments was studied by means of ToF‐SIMS depth profiling. We demonstrated that the presence of the surrounding SiO2 matrix provides a strong barrier to P diffusion and, for temperatures equal or above 1000 °C, induces P segregation in the SiO regions, where two‐dimensional layers of Si nanocrystals are formed during the thermal treatment. Such an effect is qualitatively in agreement with the P diffusivity data reported in the literature. The amount of P atoms incorporated in the Si nanocrystal region is directly controlled through a limited source process by properly adjusting the thickness of the P δ‐layer interposed between the SiO and SiO2 films. Copyright © 2012 John Wiley & Sons, Ltd.